Ketimpangan Potensi Manufaktur Antara Wilayah Utara dan Wilayah Selatan di Provinsi Jawa Tengah (2006 – 2007) - Abdul Aziz Ahmad; Kamio Kamio (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
On observation periods (2006–2007), industrialization process in Central Java looks impression. Manufacture sector in every regions in the Province showed positive growth. By Location Quotient analysis, this research founds that the mapping of manufacture sectors potency in every regions in Central java Province can be directed. It is founds that the regions where it have low competitiveness of manufacture sector and also have no potential to develop was dominated by regions in south area of Central Java. Its include Cilacap, Banyumas, Banjarnegara, Wonosobo, Temanggung, Magelang, and Wonogiri Regency. Its is also Demak, Pati Regency, and Tegal Town. Otherwise, the regions where it have high competitiveness and big potency to keep developed involve Karanganyar, Jepara, Semarang, Kendal, and Tegal Regency.Keyworlds: Location Quotient, manufacture, competitiveness